POZA INFANTYLIZACJĘ W EDUKACJI WYŻSZEJ. PRZYGOTOWANIE STUDENTÓW DO ŻYCIA W (NIE)BEZPIECZNYM SPOŁECZEŃSTWIE - Babicka-Wirkus, Anna (Rocznik Pedagogiczny, 2018)
The article deals with the problem of the infantilization of students, which takes place at universities. The starting point is the thesis that contemporary education at higher levels does not prepare stu- dents for the development of critical thinking and does not provide the skills to deal with problem- atic situations typical of global society. Instead, it approves and implements mechanisms leading to the infantilization of adults, such as: censorship, caution, language medicalization and microag- gression. In the text I analyze these dangerous phenomena and indicate the consequences that they bring, not only for the development of the institution itself, but also its autonomy, and above all the students academic growth.